Analysis of Domestic Waste Management on Water Quality Around Residential Areas - Fitriana Fitriana; Rahmat Pannyiwi (International Journal of Health Sciences, 2026)
Background: Domestic waste is one of the major environmental pollutants generated from household activities, including wastewater, kitchen waste, detergents, and organic waste. Improper domestic waste management can reduce water quality around residential areas and negatively affect public health and aquatic ecosystems. Objective: This study aims to analyze the relationship between domestic waste management and water quality around residential areas. Methods: This study used an analytical observational design with a cross-sectional approach. The research was conducted in residential areas with high domestic activity. Data regarding domestic waste management were collected through observation sheets and questionnaires, while water quality was assessed through physical, chemical, and biological examinations. Parameters analyzed included temperature, color, odor, pH, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), and coliform bacteria levels. The data were analyzed using correlation and regression analysis. Results: The results showed that most households had inadequate domestic waste management practices. Poor waste management was associated with declining water quality, indicated by increased BOD, COD, TSS, and coliform bacteria levels. Statistical analysis showed a significant relationship between domestic waste management and water quality (p<0.05). Conclusion: Improper domestic waste management contributes to water quality degradation around residential areas. Improving household waste management systems is necessary to maintain environmental quality and reduce public health risks.